Effect of the tillage systems on weed flora composition - Santín Montanyá I.; Catalán G. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
The changes from a conventional crop to a conservation tillage system can lead to shifts in weed species composition. Generally, weeds that emerge are tolerant to management practices used in agricultural areas. This can lead to the development of weed infestation that is hard to control, and ultimately to crop yield losses. A better understanding of crop production effects on weed species shifts can lead to the development of improved weed management strategies. The influence of three different tillage systems (traditional tillage, minimum tillage and direct drilling) in weed species composition of an agricultural field in Alcalá de Henares was compared in an experiment throughout twelve years. A preliminary evaluation of weed species in each tillage system shows better control of weed flora by direct drilling with respect to other systems. A study has also been performed about the changes produced in the composition of more important weed species for each tillage system.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)